Electronic circuits fundamentals and applications - Tooley, Michael H. (Routledge, 2015)
Mike Tooley provides all the information required to get to grips with the fundamentals of electronics, detailing the underpinning knowledge necessary to appreciate the operation of a wide range of electronic circuits, including amplifiers, logic circuits, power supplies and oscillators. The fourth edition now offers an even more extensive range of topics, with extended coverage of practical areas such as Raspberry Pi.